2006
DOI: 10.1111/j.1539-6924.2006.00737.x
|View full text |Cite
|
Sign up to set email alerts
|

Applying a Health Behavior Theory to Explore the Influence of Information and Experience on Arsenic Risk Representations, Policy Beliefs, and Protective Behavior

Abstract: The common sense model (CSM) shows how people process information to construct representations, or mental models, that guide responses to health threats. We applied the CSM to understand how people responded to information about arsenic-contaminated well water. Constructs included external information (arsenic level and information use), experience (perceived water quality and arsenic-related health effects), representations, safety judgments, opinions about policies to mitigate environmental arsenic, and prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(60 citation statements)
references
References 47 publications
(64 reference statements)
4
56
0
Order By: Relevance
“…This is consistent with Severtson et al (2006), who found that personal experience (perceived water quality) mitigated the influence of communicated test results and safety standards (external sources) on reducing arsenic exposure. This means that when people perceive their water as being of good quality, they will not change to an alternative source.…”
Section: Summary and Interpretation Of Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with Severtson et al (2006), who found that personal experience (perceived water quality) mitigated the influence of communicated test results and safety standards (external sources) on reducing arsenic exposure. This means that when people perceive their water as being of good quality, they will not change to an alternative source.…”
Section: Summary and Interpretation Of Resultssupporting
confidence: 92%
“…In addition, social influence on people's health-protective behavior was included in compliance with Ajzen's Theory of Planned Behavior. Finally, two possible behavior determinants that proved influential in previous studies were also investigated: (a) money contributed for the deep tubewell's installation (WSP and UNICEF, 2007) and (b) whether the shallow tubewell was perceived as arsenic contaminated (Severtson et al, 2006). We classified the derived fostering and hindering factors into the categories of personal, social, and situational behavior determinants and, in accordance with the Protection Motivation Theory, assume the following relationships between these factors and deep tubewell use.…”
Section: Health-protective Behaviormentioning
confidence: 99%
“…We allowed error terms for endogenous variables within a particular stage in the model to covary if they had strong bivariate correlations (e.g., between attitude items; empathy with sadness response). In the initial model, fit indices were not adequate: SRMR ¼ 0.14 (<.10 adequate), CFI ¼ .69, NFI ¼ .68 (>.90 adequate); v 2 =df ¼ 6.70 (<3.0 adequate) and RMSEA ¼ .22 (<.08 adequate; Severtson et al, 2006). None of the paths between control variables (smoking status and gender) and proximal variables were statistically significant.…”
Section: Path Model Resultsmentioning
confidence: 91%
“…Path modeling is especially useful when examining chains of causation between independent variables and outcome variables that are mediated through indirect effects (Severtson, Baumann, & Brown, 2006). The model included direct paths between exogenous control variables (smoking status and gender) and each proximal outcome.…”
Section: Path Model Resultsmentioning
confidence: 99%
“…These results are consistent with those of previous studies. Severtson et al [28] investigated the relationship between health consequences and emotions and suggested that beliefs about health consequences may be linked more to intuitive than analytical processing. Considering that health information is processed experientially, Epstein [29] notes that experimental processing is linked with affect, while analytical processing is described as affect-free.…”
Section: Differences On Aggregate Levelmentioning
confidence: 99%